Physicochemical Properties and Structural Study of Heat Treatment-Modified Chinese Yam (Dioscorea opposita Thunb.) Starch–Ferulic Acid Complexes - Sandu Xie; Yanping Lei; Huiqing Chen; Shuqi Liu; Xiaojuan Lin; Zebin Guo; Yi Zhang; Baodong Zheng (Foods)
In this study, complexes of pregelatinized Chinese yam starch with ferulic acid (PCYS+FA) were prepared using a boiling water bath, with varying levels of Chinese yam starch (CYS) and ferulic acid (FA). The investigation focused on the effects of FA addition (3%, 9%, and 15%) on the physicochemical properties and structure of PCYS+FA complexes. The solubility, swelling, and water-holding capacity of PCYS+FA were compared with those of CYS, with the solubility and swelling showing a gradual enhancement with increasing FA content. The incorporation of FA reduced the thermal stability of CYS, decreasing the initial degradation temperature from 245.94 °C (CYS) to 228.17 °C (PCYS+15%FA). Infrared spectroscopy revealed that CYS and FA were bound through non-covalent intramolecular hydrogen bonding. Furthermore, X-ray diffractograms showed that FA and CYS formed a V-type complex, in which the crystallinity of PCYS reached a minimum of 3.72%, and the degree of molecular ordering was reduced. Scanning electron microscopy analysis demonstrated that FA adhered to the surface of starch granules, resulting in the formation of pores that facilitated the entry of FA molecules into the internal crystal region of starch, allowing them to interact with starch molecules.